Pengaruh Penerapan Metode Hypnoteaching Pada Siswa ABK Terhadap Peningkatan Hasil Belajar di Kelas II SD Negeri 8 Sakayu Musi Banyuasin - Sambia Sambia; Abd Hadi; Muhammad Hambal Shafwan (Dinasti Review, 2024)
This research is motivated by the low academic achievement in Islamic education, which is attributed to the use of conventional and monotonous teaching methods such as lectures, question and answer sessions, and assignments. This has led to student boredom and negatively impacted their learning outcomes. Therefore, diverse and engaging teaching approaches are needed to capture students' attention and enhance their understanding of the material, thus improving their academic performance. In this study, an experiment was conducted using the Hypnoteaching method, which integrates various approaches such as Multiple Intelligences and student creativity, to identify and develop their potential, talents, intelligence, and creativity. The education sector requires a variety of teaching methods to stimulate students' development. Currently, there is a trend where students solely focus on mechanical understanding of content material without considering its impact on their learning attitudes. This research combines two types of approaches, namely field research and library research. The research findings indicate that the implementation of the hypnoteaching method has a positive influence on the academic performance of second-grade students at SD Negeri 8 Sekayu Musi Banyuasin.